Comparative Study of Variations in Oxidizing Agents on the Quality of Briquettes from Songgon Coconut Shells, Banyuwangi Regency: Studi Perbandingan Variasi Zat Pengoksidasi Terhadap Kualitas Briket Dari Tempurung Kelapa Songgon Kabupaten Banyuwangi - Malis, Eko; Ridho, Rosyid; Ayun, Qurrata; Eka Evi Susanti, Reni (Jurnal Kimia dan Rekayasa, 2024)
Research has been carried out on the preparation of a Comparative Study of Variations in Oxidizing Substances on the speed of ignition of briquettes from Songgon Coconut Shell, Banyuwangi Regency. To determine the ignition time, several oxidizers NaNO2, KNO3 and K2Cr2O7 were used. The percentage of oxidizing agent is 10, 15, 20, 25, 30 %. Coconut shell briquettes are obtained through conventional pyrolysis in a wood-burning stove for 12 hours with liquid smoke as a byproduct. The adhesive used in this research was starch with its own variations 15 %. The characteristics of the briquettes produced include: ignition time, burning time, and water content. From the characterization results it can be seen that the best oxidizer used is K2Cr2O7 oxidizer with a concentration of 25%, flame time of 9 seconds. The best burning time is with the addition of the oxidizer Sodium NItrite, namely 18650 seconds, at a concentration of 5%. The ash content increases as the oxidizer increases. The briquettes produced are in accordance with SNI No. 1/6235/2000, namely &#8804 9%. The water content of the briquettes produced was smallest with the addition of the oxidizer K2Cr2O7 at 4.2% with a concentration of 5%. Abstrak Telah dilakukan penelitian preparasi Studi Perbandingan Variasi Zat Pengoksidasi Terhadap kecepatan waktu Nyala briket dari Tempurung Kelapa Songgon Kabupaten Banyuwangi. Untuk mengetahui waktu nyala digunakan beberapa oksidator NaNO2, KNO3 dan K2Cr2O7 . Persentase oksidator dilakukan yaitu10, 15, 20, 25, 30 (dalam %). Briket tempurung kelapa diperoleh melalui pirolisis konvensional dalam tungku yang dibakar dengan kayu bakar selama 12 jam dengan hasil samping liquid smoke. Perekat yang digunakan pada penelitian ini Tepung kanji dengan variasi masing-masing 15 %. Karakterisasi dari briket yang dihasilkan antara lain : waktu nyala, lama pembakaran, dan kadar air. Dari hasil karakterisasi dapat diketahui bahwa dari oksidator yang dipakai yang terbaik adalah osidator K2Cr2O7 dengan konsentrasi 25 %, waktu nyala 9 sekon. Lama pembakaran terbaik adalah dengan penambahan oksidator Natrium NItrit yaitu 18650 sekon, pada konsentrasi 5%. Kadar abu meningkat seiring peningkatan oksidator. Briket yang dihasilkan sudah sesuai berdasarkan SNI No. 1/6235/2000 yaitu &#8804 9%. Kadar air dari briket yang dihasilkan terkecil dengan penambahan oksidator K2Cr2O7 sebesar 4,2% dengan konsentrasi 5%